CdSe Species Decorated TiO2 Nanotubes Film Via Chemical Bath Deposition for Enhancing Photoelectrochemical Water Splitting Performance - Lai, Chin Wei; Lau, Kung Shiuh; Samad, Nur Azimah Abd; Chou, Pui May (Bentham Science Publishers, 2018)
Background: The conversion of sunlight to electrical power has been dominated by solidstate junction devices, often made of silicon. However, this dominance is now being challenged by the emergence of the new generation of water splitting cell (integration of photovoltaic system with an electrolyzer to generate clean and portable H2 energy carrier. This cell normally is based on nanocrystalline materials, which offers the prospect of cheap fabrication together with other attractive feature such as high chemical stability and flexibility in aqueous solution under evolving oxygen (O2) gases. However, nanocrystalline materials are facing few drawback such as recombination losses of charge carriers and less response under visible spectrum. Therefore, an effort to minimize the recombination losses of charge carriers and extended the spectral response of TiO2 NTs into visible spectrum by incorporating an optimum amount of lower band gap and suitable band edge position semiconductor (cadmium selenide [CdSe]) into the lattice of TiO2 NTs. Methods: An efficient approach has been demonstrated in this research work to enhance the solardriven photoelectrochemical (PEC) water splitting performance by decorating CdSe species into highly ordered TiO2 nanotubes (NTs) film through a facile and cost-effective chemical bath deposition. Morphology, chemical properties, and electronic structures have been studied. Results: A maximum photocurrent density of ~2.50 mA/cm2 at 0.6V versus Ag/AgCl electrode was exhibited by TiO2 NTs with the presence of approximately 1 at % of CdSe species. The presence of CdSe species offered an improvement of photocurrent density under solar irradiation due to the effective mediators to trap the photo-induced electrons and minimizes the recombination of charge carriers within the lattice of TiO2 NTs. Conclusion: Hybrid CdSe-TiO2 NTs were successfully fabricated through chemical bath deposition method in order to study the synergistic coupling effect of CdSe with TiO2 NTs on the PEC performance. By bathing pure TiO2 NTs film in a 5 mM CdSe precursor solution extensively covered by approximately 1 at % CdSe exhibited the highest jp of 2.50 mA/cm2 among the samples. However, excessive deposition (≥5 mM) was neither negatively affected by the self-organized NTs nor decreased in jp. This condition inferred that higher ionic product (Cd and Se ions) leaded to rapid ion-by-ion condensation or adsorption of colloidal particles clogged the opening pore’s mouth of TiO2 NTs. Thus, an improvement in the photoresponse was observed when optimum amount (~ 1 at %) of the CdSe was deposited on TiO2 NTs film.